VALIDASI MODUL BEHAVIORAL ACTIVATION DALAM MENINGKATKAN MANAJEMEN DIRI PASIEN HIPERTENSI DI PUSKESMAS - , Muharini Aulia, Prof. Dra. Kwartarini Wahyu Yuniarti, Mmed.Soc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Hypertension was one of many types of chronic diseases experienced by Indonesian people, especially Yogyakarta. Based on the data obtained from Department of Health, Sleman, there were more than 100 cases oh hypertension in 2013. This fact confirms the importance of developing appropriate treatment model for patiens with hypertension. In addition to medical treatment, psychological treatment with the goal of improving patient self manajement capabilities also play an important role to improve patients quality of life. Behavioral activation is a treatment with behavioral approach that focuses on improving the expected behavior through structured behavioral activation. The purpose of this study was to validate behavioral activation modul in improving hypertensive patients self management (jogging, aerobic and taking antihypertensive medication) in health center. This study used untreated control group with pretest and posttest design. There were 8 psychologist from 8 health center in Sleman involved in this study. 4 of them ellected to use behavioral activation treatment while the other 4 did not deliver the treatment. Participant in this study were 8 people diagnosed with hypertension and have poor self management. The instrumen for data collecting in this study are behavioral checklist and Beck Depression Inventory (BDI). The result indicates the difference of self management (Sig. .002) between the experimental group and the control group. Participants in the experimental group has a higher jogging duration (mean. 40,48 minutes/day) and taking medication (mean. 6 times/week) than the control group. Implications of these findings, study limitations and suggestions are discussed.